AB0355 Real Clinical Experience with Abatacept, from Intravenous To Subcutaneous. (15th July 2016) - Nieto-González, J.C.; Janta, I.; Ovalles-Bonilla, J.G.; Serrano, B.; Mata, C.; González-Benítez, R.; Valor, L.; Lόpez-Longo, F.J.; González-Fernández, C.M.; Monteagudo, I.; Naredo, E.
Abstract : Background: Abatacept, a fusion protein CTLA4Ig1 that selectively modulates coestimulation of T lymphocites, was approved for the treatment of active rheumatoid arthritis (RA) in 2010 as an endovenous (e.v.) biologic therapy. Three years later was approved the subcutaneous (s.c.) abatacept for RA. The efficacy and safety of both types of administration of abatacept is similar 1 . Also switching from e.v. to s.c. administration of abatacept is effective and safe according to clinical trials 2 . Real clinical practice sometimes differs from clinical trials results. To the best of our knowledge, there is a lack of studies based on real clinical experience about RA patients who switched from e.v. to s.c. abatacept. Objectives: To describe the efficacy of switching from e.v. to s.c. abatacept in our RA patients, evaluated by clinical and ultrasound examination Methods: This observational study was conducted at the rheumatology department of Hospital Gregorio Marañόn, Madrid, Spain. Patients diagnosed with RA under treatment with e.v. abatacept in whom rheumatologist and patient consensually decided to switch to s.c. abatacept were included in the study. Subcutaneous abatacept was started one month later to the last e.v. administration, corresponding to baseline in the study. At baseline and three months later, all patients were clinically assessed and underwent to ultrasound (US) examination. US examination consisted on a reduced joint count (elbows, wrists, 2nd and 3rd metacarpophalangeal, knees and ankles) and tendon examination (2nd, 4th and 6th extensor compartments and tibialis posterior and peroneal tendons). Global synovitis was calculated on B mode and Power Doppler (SBM and SDM), also for tenosynovitis (TBM and TBM). After one year from the switching, clinical reports were reviewed to collect clinical data. All patients signed an informed consent before to be included. This study was approved by our ethics committee. Results: We included 23 RA patients, from them 21 (91.3%) are still on s.c. abatacept. Twenty-two from 23 (95.7%) were females, mean age 60 years old (range 44.1–82.4) and mean time on e.v. abatacept was 2 years (range 0.8–7.1). SBM was greater at 3 months after switching in 81.9% (18/22) of patients. No differences between SDM, TBM nor TDM were seen at three months. One patient had active synovitis on US both at baseline and three months. She stopped abatacept after US at three months. Four patients were receiving half dose of e.v. abatacept (5 mg/kg every month) and switched to s.c. abatacept 125 mg every other week. All four patients are still on the same regimen. Table 1 shows clinical and ultrasound data at baseline and follow-up. Conclusions: Switching from e.v. to s.c. abatacept in our RA patients was succesful at 12 months. Ultrasound on B mode showed more synovitis at 3 months after swiching, without relation with flares at 12 months. References: Genovese MC. J Rheumatol. 2014;41:629–39 Keystone EC. Ann Rheum Dis. 2012;71:857–61 Naredo E. Arthritis Rheum. 2008;59:515–22 Disclosure of Interest: None declared